2017
DOI: 10.18203/issn.2454-5929.ijohns20174325
|View full text |Cite
|
Sign up to set email alerts
|

Hadad-Bassagasteguy flap in reconstruction of skull base defects after endonasal skull base surgery

Abstract: INTRODUCTIONIn the patients with large dural defects of anterior and ventral skull base, there is a significant risk of postoperative cerebrospinal fluid (CSF) leak. Reconstruction with the vascularised tissue is desirable to facilitate rapid healing, especially in irradiated patients. HadadBassagasteguy flap (HBF), a vascular pedicled flap of the nasal septum mucoperiosteum and mucoperichondrium based on the posterior septal artery (branch of sphenopalatine artery), was first developed in university of Rosari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In a study involving twenty-five patients who had expanded endonasal approach (EEA) surgeries with the use of NSF, Wardas et al [21] reported a nonanticipated postoperative CSF leakage in 2 cases. Singh et al [22] assessed 53 patients who received Hadad-Bassagasteguy flap (HBF) to restore anterior skull base lesions among patients with high-flow on-table CSF leak and found that only 2 of the total patients (2/53; 3.8%) experienced a post-operative CSF fluid leak. They concluded that patients with high-flow intraoperative CSF leak can benefit significantly from the use of HB posterior nasal septal flap for rebuilding of anterior skull base.…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving twenty-five patients who had expanded endonasal approach (EEA) surgeries with the use of NSF, Wardas et al [21] reported a nonanticipated postoperative CSF leakage in 2 cases. Singh et al [22] assessed 53 patients who received Hadad-Bassagasteguy flap (HBF) to restore anterior skull base lesions among patients with high-flow on-table CSF leak and found that only 2 of the total patients (2/53; 3.8%) experienced a post-operative CSF fluid leak. They concluded that patients with high-flow intraoperative CSF leak can benefit significantly from the use of HB posterior nasal septal flap for rebuilding of anterior skull base.…”
Section: Discussionmentioning
confidence: 99%